Sensory Quality Analysis Of Putu Ayu Cake With The Addition Of Red Dragon Fruit Extract - Rahmi Kurnia; Lucy Fridayati; Elida Elida; Ezi Anggraini (Universitas Negeri Padang, 2025)
Synthetic dyes that are often used in making putu ayu cakes can be harmful to health because they contain sulfuric acid or citric acid chemicals, so safer natural dye alternatives are needed. Red dragon fruit contains anthocyanins, antioxidants, and essential nutrients that can be used as natural dyes while providing added value in terms of product health and aesthetics. This study aims to analyze the sensory quality of putu ayu cakes with the addition of red dragon fruit extract of 20%, 30%, and 40%. The type of research used was a pure experiment with a Completely Randomized Design (CRD) and three times. The research sample consisted of three treatments and one control, assessed by five semi-trained panelists, namely lecturers from the IKK Department of Culinary Arts, UNP. Data were obtained through organoleptic tests including color, aroma, and taste using an instrument in the form of an assessment sheet. Data analysis techniques were carried out quantitatively inferentially. The results showed that the addition of 40% red dragon fruit extract had the most significant effect on color, aroma and taste (dragon fruit), but did not have a significant effect on the sweetness of putu ayu cakes.